Reading in the Digital Age: An Empirical Examination of Digital Literacy's Significance for UIN Suska Riau Students Using SEM Path Analysis - Pangoloan Soleman Ritonga; Arif Yasthophi; Paijan Rambe; Wimbi Apriwanda Nursiwan; Syahrul Amin; Nurhidayat Nurhidayat; Tazkiyatunnafs Elhawwa (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
The digital literacy is likely playing a crucial role on the reading interest in this digital age. This study aimed to determine the influence of digital literacy on the reading interest of UIN Suska Riau students. The sample of this study comprised of 82 students of UIN Suska Riau and the data were collected using questionnaires. The collected data were analyzed using Structural Equation Modeling (SEM) Path Analysis 3.0 and SPSS 21. The results showed that digital literacy had a significant influence on the reading interest of UIN Suska Riau students. This showed that the path coefficient value of the original sample estimate (beta) was positive at 0.471, and the direction of the relationship between both variables was in the quite strong category. The effect of digital literacy on the reading interest was also significant in the 2-way test (t table = 1.97) with a t-statistic value of 8.105, which was greater than the t table, and a p-value lower than alpha 5% (0.000 < 0.05). Overall, the results of this analysis proofed that the digital literacy positively related to the rading interest and it significantly influenced the reading interest.